Integrating Local Cultural Content to Enhance EFL Students’ Collaborative Writing: An Explanatory Sequential Mixed-Methods Study - Aprianto, Dedi; Sutarman, Sutarman (JOLLT Journal of Languages and Language Teaching, 2026)
In EFL learning, collaborative writing is the joint production of a text in which two or more learners actively contribute to planning, drafting, and revising a shared written product. In multicultural settings such as Indonesia, integrating local cultural content is assumed to enhance engagement and collaboration; however, its effect on learners’ collaborative writing performance within the Sasak cultural context remains underexplored. This study examined the impact of embedding local cultural content into writing instruction on EFL students’ collaborative writing performance. Employing an explanatory sequential mixed-methods design, quantitative data were collected from 134 students in the Department of Computer Science at Bumigora University, and 20 students were purposively selected for semi-structured interviews to provide qualitative insights. Quantitative analyses indicated significant improvement in writing performance, with mean scores increasing from 66.62 to 72.01 (p < .05) and a strong positive correlation between pre- and post-test scores (r = .736, p < .05). The effect size, Cohen’s d = 0.84, confirmed a large improvement. Qualitative findings revealed that cultural familiarity strengthened group engagement, boosted identity-based confidence, and facilitated idea generation. Students reported that working with culturally familiar themes encouraged inclusive participation, reduced communication anxiety, and increased motivation. These findings suggest that integrating local cultural content enhances both language development and collaborative processes. Two key implications emerge: (1) Curriculum designers should incorporate localized cultural materials to increase contextual relevance, and (2) Teachers should design collaborative activities leveraging learners’ cultural knowledge to foster richer interaction, lower participation barriers, and improve overall learning outcomes.